Role of multiplex PCR in the early diagnosis of infective endocarditis - Omnia A. Eltantawy; Amany M. Kamal; Lamyaa E. Allam; Nadia M. Elsheshtawy (Novel Research in Microbiology Journal)
Infective endocarditis (IE) is a serious infection of the endocardium and heart valves that necessitate early diagnosis. The conventional blood culture has lots of false-negative results besides being time consuming. Polymerase chain reaction (PCR) is a rapid diagnostic tool that helps in saving the patients’ life. This study aimed to investigate the feasibility of multiplex PCR in early diagnosis of IE compared to the conventional blood culture, and to evaluate its impact on IE diagnosis in cases of negative blood cultures. The current study was conducted on 30 patients admitted to the Cardiology Department, Faculty of Medicine, Ain Shams Hospitals, Cairo, Egypt, which were diagnosed clinically as infective endocarditis according to the modified Duke’s criteria. After processing of the patient's blood samples, the blood cultures recorded positivity in 5 cases (16.7 %). The most common recovered bacteria were, Staphylococcus aureus 2(6.7 %), Staphylococcus epidermedis 1(3.3 %), Enterococcus faecalis 1(3.3 %), and Escherichia coli 1(3.3 %); however, no other pathogens were isolated. On the other hand, results of multiplex PCR showed positivity in 13 cases (43.3 %), mainly; Staphylococcus aureus 5(16.7 %), E. faecalis 3(10 %), Staphylococcus epidermidis 2(6.7 %), Pseudomonas aeruginosa 2(6.7 %), and E. coli 1(3.3 %). No other bacterial of fungal pathogens were detected by multiplex PCR. Finally, the multiplex PCR assay exhibited remarkable sensitivity and feasibility in IE diagnosis over blood culture, besides being a rapid and accurate diagnostic assay that enhances proper treatment.